2007
DOI: 10.1007/s00417-007-0607-4
|View full text |Cite
|
Sign up to set email alerts
|

Retinal pigment epithelium and choroid translocation in patients with exudative age-related macular degeneration: long-term results

Abstract: Background To study the results of the translocation of a free autologous retinal pigment epithelium (RPE)-choroid graft after removal of a subfoveal choroidal neovascular membrane in patients with exudative age-related macular degeneration (AMD), and to determine whether preoperative variables may predict visual outcome at 1 year after surgery. Methods Prospective interventional case series of 84 eyes of 83 consecutive eligible patients with exudative AMD with a minimal follow-up of 1 year after surgery. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
1
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 37 publications
8
69
1
6
Order By: Relevance
“…Using various techniques to study fixation, previous studies have also shown 40 to 74% of eyes achieved fixation over the graft. [34][35][36][37][38][39] Similar to that reported by Maaijwee et al, we also found that fixation stability may worsen or improve during follow-up. 40 The reason for worsening of fixation stability may be related to delayed cystic change or atrophy whereas improvement in stability may be related to adaptation to eccentric fixation and viewing.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Using various techniques to study fixation, previous studies have also shown 40 to 74% of eyes achieved fixation over the graft. [34][35][36][37][38][39] Similar to that reported by Maaijwee et al, we also found that fixation stability may worsen or improve during follow-up. 40 The reason for worsening of fixation stability may be related to delayed cystic change or atrophy whereas improvement in stability may be related to adaptation to eccentric fixation and viewing.…”
Section: Discussionsupporting
confidence: 77%
“…33 They found the mean VA improved from 0.95 logMAR at baseline to 0.89 logMAR at 1 and 2 years and 0.79 logMAR at 3 years (n = 84, 45 and 24 patients, respectively). They showed, with a Kaplan-Meier plot that the percentage of eyes loosing < 3 ETDRS lines was 70-80% at 1 year and stabilises at around 50% at 2 to 4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peripheral RPE patches seem to have good long-term survival, and the visual results are reasonable. 61 The introduction of anti-VEGFs revolutionised the treatment of CNV in ARMD, and the indications for vitreoretinal surgery reduced considerably. There are a few remaining indications such as RPE rips and subretinal haemorrhages, but very few cases are being done.…”
Section: Submacular Surgerymentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Since in vivo an equilibrium of neurotrophic factors, such as pigment epithelium-derived factor (PEDF), fibroblast growth factor, platelet-derived growth factor and others, supports the survival of neural tissues, it may be necessary to transplant cells that have been genetically modified to express these factors to achieve optimal functional improvement. In fact, in vitro and in vivo studies have shown that supplementation with various growth factors prevents or delays photoreceptor degeneration and increases the function of dopaminergic tissue in animal models of retinal degeneration and PD.…”
Section: Introductionmentioning
confidence: 99%